Integrating post-editing into the subtitling classroom: what do subtitlers-to-be think? - Bolaños García-Escribano, Alejandro; Díaz-Cintas, Jorge (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2023)
In today’s professional landscapes, new technologies have altered media localization workflows as much as practitioners’ workstations and habits. A more comprehensive integration of automation tools, including (neural) machine translation systems, has been ushered in by the proliferation of cloud ecosystems. In a further technological drive in the production of subtitle projects, systems now integrate automatic speech recognition and can machine translate subtitles from pre-spotted templates. The rise of post-editors in media localization, specifically in subtitling, has been a reality for some time now, triggering the need for up-to-date training methods and academic curricula. It is against this backdrop that this article seeks to examine the perception of post-editing among trainees in subtitling. A total of four teaching experiences, conceived as practical experiments in interlingual subtitle post-editing (English into Spanish), involving postgraduate students from both Spain and the United Kingdom, are described here. The sample comprised 36 master’s-level students enrolled in translator training programmes that have a focus on audiovisual translation. A mixed-methods approach was adopted for this study; after each experience, the feedback collated through online questionnaires has proved paramount to understanding the participants’ opinions about post-editing in the subtitling classroom. Interestingly, most of the respondents believe that subtitle post-editing training should feature more prominently in translation curricula even though they have voiced their reluctance to undertake post-editing work professionally.